2013
DOI: 10.1111/boj.12040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic analysis ofTulipa(Liliaceae) based on noncoding plastid and nuclear DNA sequences with an emphasis on Turkey

Abstract: We investigated the phylogenetic relationships in Tulipa in Turkey using DNA sequences from the plastid trnL‐trnF region and the internal transcribed spacer (ITS) of nuclear ribosomal DNA. We generated trnL‐trnF and nuclear ITS sequences for 11 Tulipa spp. from Turkey and compared the utility of trnL‐trnF and ITS sequences for phylogenetic analysis. Neighbor‐joining, Bayesian and maximum parsimony methods were implemented using the same matrices. Our study of Tulipa based on molecular data revealed congruent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
7
16
0
Order By: Relevance
“…Monophyly of Tulipa , excluding Amana , was well supported and agrees with previous analyses of the genus (Fay et al ., ; Türktaş et al ., ). Amana , although sharing morphological characters with Tulipa and Erythronium , appears to be sister to (or possibly embedded in) Erythronium (Clennett et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Monophyly of Tulipa , excluding Amana , was well supported and agrees with previous analyses of the genus (Fay et al ., ; Türktaş et al ., ). Amana , although sharing morphological characters with Tulipa and Erythronium , appears to be sister to (or possibly embedded in) Erythronium (Clennett et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Türktaş et al . () presented a molecular phylogenetic study based on species from Turkey, but their study lacked some critical taxa needed to address the remaining questions.…”
Section: Taxonomic History Of Tulipamentioning
confidence: 99%
“…The tulip originated in Turkey and was introduced into Western Europe in the mid-16 th century (Garber, 2016). In Turkey, the tulip is an ornamental plant of major economic importance (Turktas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…() and Turktas et al . () published phylogenetic analyses of Tulipa L., the former including a taxonomic treatment of the whole genus and the latter focusing on Turkish species, and Qi et al . () demonstrated that Heterosmilax Kunth is embedded in Smilax L. (Smilacaceae).…”
mentioning
confidence: 99%